VD_FINDINFO HC / 2018 / 690 vom 27. August 2018 - VD Tribunal cantonal (2018)
DIVORCE, OBLIGATION D'ENTRETIEN, ENFANT, CONJOINT, RÉGIME MATRIMONIAL | 125 CC, 205 CC, 206 CC, 285 CC, 651 al. 2 CC, 301a CPC (CH)